Pengaruh Modifikasi Papan Tolakan yang Ditinggikan terhadap Lompat Jauh Gaya Jongkok pada Siswa SDN 06 Tegalsari Kecamatan Ampelgading Kabupaten Pemalang - Toto Suyitno; Didi Muhtarom; Boby Agustan (Universitas Palangka Raya, 2024)
Long jump is one of the branches of athletics. As we know, athletics involves physical activities or exercises that consist of natural movements such as walking, jumping, and throwing. Various methods in athletics have been practiced since the early history of humankind. History indicates that in ancient classical times, athletics was conducted in an organized and structured manner, and over time, its programs underwent changes and improvements based on healthy ideas. Today, athletics is a complex sport that includes various tests based on the requirements of its implementation. Observation results show that a long jump athlete is required to achieve maximum jumps (distance), which is measured from the take-off board to the nearest point of landing. Preliminary studies revealed that students were not achieving optimal results in long jump performances. The evident obstacles include a lack of facilities and infrastructure to support long jump training and a shortage of qualified teachers to instruct physical education. As a result, the training techniques used appear monotonous and boring for the students. Thus, the research question posed is: what is the effect of modifying the take-off board on the results of the squat-style long jump among students of SDN 06 Tegalsari, Ampelgading District, Pemalang Regency? The method used in this study is the experimental method. Theoretically, the definition of an experiment according to Umar (2018:161) is